The Influence Of The Application Of Dende Games On The Locomotor Abilities Of Children Aged 5-6 Years - Darfin, Sutra Awaliyah; Baharuddin, Baharuddin; Alwi, Besse Marjani; Mardiah, Mardiah; Mukhlisah, Mukhlisah (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2025)
The dende game as a traditional game not only has educational value, but also a means of cultural preservation that can be integrated in early childhood learning activities in a contextual and fun way this game is played in groups and involves physical activity. Using a quantitative approach and quasi-experimental design, this study involved two classes in group B at Jaya Purnama Kindergarten, Bulukumba Regency, consisting of 12 children as the experimental group and 12 children as the control group. The Dende game was implemented in the experimental group with 8 times of treatment intervention, while the control group received regular learning without special treatment. The data collection instrument used an observation sheet containing indicators of children's locomotor abilities. Data were analyzed using descriptive statistics and independent sample t-test to determine differences between the two groups. The results of hypothesis testing using independent sample t-test showed that there was a significant difference between the two groups. Based on the analysis conducted using SPSS 23 IBM, the t_hitung value was 29.472, while the t_table was 1.717 with a Sig. value of 0.00 <0.05. The intervention given to the experimental class had a positive effect in improving children's locomotor abilities compared to the control class, so it can be concluded that the dende game has a significant effect in improving children's locomotor abilities, with a significant increase in balance, muscle strength, agility